2020
DOI: 10.1002/jwmg.21944
|View full text |Cite
|
Sign up to set email alerts
|

Spatial Scale and Shape of Prescribed Fires Influence Use by Wild Turkeys

Abstract: In recent years, there have been increasing efforts to understand effects of prescribed fire on population dynamics of wild turkeys (Meleagris gallopavo; turkeys) in pine (Pinus spp.) forests. Although distribution of turkeys is not limited to pine forests, these forests provide nesting and brood-rearing habitat throughout the southeastern United States. Previous studies have investigated direct (e.g., nest loss to fire) and indirect (e.g., nest-and brood-site selection) effects of prescribed fire, but little … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
1
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 63 publications
0
1
0
Order By: Relevance
“…However, edge species are likely to have some threshold in burn-block size where habitat components within the burn block interior are too far from those provided in unburned areas, rendering the interior portion of the burn block unusable. For example, Cohen et al (2019) demonstrated that eastern wild turkeys (Meleagris gallopavo, Linnaeus 1758) were unlikely to use the interior of burn blocks when greater than 250 m from an unburned edge, and Sullivan et al (2020) found that turkey use was highest in smaller burn blocks (23 ha). Even so, this species is capable of traveling much longer distances, and fire consistently produces desirable plant community structure for that species (Chance et al 2019).…”
Section: Dispersion Of Wildlife Habitatmentioning
confidence: 99%
“…However, edge species are likely to have some threshold in burn-block size where habitat components within the burn block interior are too far from those provided in unburned areas, rendering the interior portion of the burn block unusable. For example, Cohen et al (2019) demonstrated that eastern wild turkeys (Meleagris gallopavo, Linnaeus 1758) were unlikely to use the interior of burn blocks when greater than 250 m from an unburned edge, and Sullivan et al (2020) found that turkey use was highest in smaller burn blocks (23 ha). Even so, this species is capable of traveling much longer distances, and fire consistently produces desirable plant community structure for that species (Chance et al 2019).…”
Section: Dispersion Of Wildlife Habitatmentioning
confidence: 99%
“…Many organisms are drawn to edges because they can use each habitat to meet different needs (Wiens 1976;Harris 1988). However, the amount of edge and area within a burned or unburned patch affects habitat use differently (Sullivan et al 2020) and can facilitate predation on some organisms. Habitat use can therefore be influenced by tradeoffs, such as the one between needing food and risking attack by predators (Cherry et al 2017).…”
Section: Prescribed Fire Sizementioning
confidence: 99%
“…For example, research suggests that burn blocks of 40-60 acres, with 50% of them burned annually, support nesting areas and food for northern bobwhite quail (Palmer and Sisson 2017;Rosche et al 2019). Studies recommend burning 12%-33% of burn blocks (Wann et al 2020) that are between 50 and 500 acres (Chamberlain 2019;Sullivan et al 2020) to support habitat needs when managing wild turkeys. If management objectives include supporting a broader variety of species, consider changing the size of a fire in a given area for each burn.…”
Section: Management Considerationsmentioning
confidence: 99%